A case‐control study and meta‐analysis reveal the association between COX‐2 G‐765C polymorphism and primary end‐stage hip and knee osteoarthritis. Issue 6 (17th February 2018) - Huang, Wei; Deng, Chen; Tian, Feng; Gao, Weilu; Ding, Zhenfei; Rao, Xianliang; Yin, Zongsheng
Abstract : Background: Osteoarthritis (OA) is a popular arthrosis featured as pain, limited joint activity, and deformity. Cyclooxygenase‐2 (COX‐2) has been reported to be up‐regulated in arthritic tissues and is integral to the progression of osteoarthritis (OA). Previous studies showed the COX‐2 promoter G‐765C polymorphism could influence COX‐2 expression. However, the relationship between the variant and OA risk is contrasting. Methods: We conducted a case‐control study with 196 primary end‐stage hip and knee OA cases and 196 controls in a Chinese Han population. Subsequently, we integrated this case‐control study in a meta‐analysis to acquire greater statistical power. The results from our case‐control study using MassARRAY genotyping technology and binary logistic regression statistical methods. Results: The variant carriers in the Chinese Han population had a lower primary end‐stage hip and knee OA susceptibility (C vs G: OR = 0.350, 95%CI: 0.154‐0.797, P  =   .012; GC vs GG: adjusted OR = 0.282, 95%CI: 0.118‐0.676, P  =   .005). Stratification studies indicated that a higher GC frequency in women decreased not only knee OA susceptibility but also unilateral knee OA risk. The meta‐analysis showed that the variant exhibited a significantly decreased OA risk through comparisons involving allelic, homozygous, heterozygous, and dominant models. Conclusion: Our findings suggest that the COX‐2  G‐765C polymorphism exerts a protective effect against primary end‐stage knee osteoarthritis in a female Chinese Han population.